Installing the tree trunk for the ritual - Mumbai Archive Project Team (Jio Institute, 2024)
The ground where the tree trunk is installed is purified using cow dung and holy water. The tree trunk is erected by placing it in a hole dug in the ground and secured into position using ropes.